2020
DOI: 10.1021/acs.jpcc.0c07792
|View full text |Cite
|
Sign up to set email alerts
|

BiF3 Incorporation in Na/Ba Mixed Network Modifier Fluoride–Phosphate Glasses: Structural Studies by Solid-State NMR and Raman Spectroscopies

Abstract: Bismuth-containing rare-earth codoped fluoride phosphate glasses are promising materials for superbroadband near-infrared (NIR) emission with potential applications in optical amplification. To elucidate their structural organization, this contribution develops a comprehensive multinuclear solid-state single and 31P/19F double resonance NMR strategy, applied to glasses in the system (BiF3) y (50NaPO3–20Ba­(PO3)2–20NaF–10BaF2)100–y (y = 0, 5, 10, 20, 30, 40). To separately assess the influence of bismuth and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
(88 reference statements)
1
6
0
Order By: Relevance
“…In general, the 19 F chemical shifts measured in this system are much more positive than those measured in other types of fluorophosphate glasses containing group-12 and 13 elements. 68,[73][74][75] On the other hand, some of such previously measured fluorophosphate glasses had also shown weak signals in the −70 ppm region, which could be assigned to P-bonded fluorine species based on 19 F { 31 P} REDOR data and the comparison with crystalline Na 2 PO 3 F. 68,[73][74][75] For the present glasses Fig. 11 illustrates an analogous comparison of 19 F{ 31 P} REDOR data for some representative glasses.…”
Section: Paper Dalton Transactionssupporting
confidence: 51%
See 1 more Smart Citation
“…In general, the 19 F chemical shifts measured in this system are much more positive than those measured in other types of fluorophosphate glasses containing group-12 and 13 elements. 68,[73][74][75] On the other hand, some of such previously measured fluorophosphate glasses had also shown weak signals in the −70 ppm region, which could be assigned to P-bonded fluorine species based on 19 F { 31 P} REDOR data and the comparison with crystalline Na 2 PO 3 F. 68,[73][74][75] For the present glasses Fig. 11 illustrates an analogous comparison of 19 F{ 31 P} REDOR data for some representative glasses.…”
Section: Paper Dalton Transactionssupporting
confidence: 51%
“…21,61–67 In turn, the phosphate glass network may be composed of up to four different types of [PO n ] polyhedra. In mixed network former systems, these are denominated by the P n m x terminology, where n is the number of bridging O atoms connecting to other network formers while m denotes the number of these linkages connecting the phosphate polyhedron with the specific network former species X; 68 this reference also states the relationship to the Q n terminology used for single-network former phosphate glasses. 69…”
Section: Resultsmentioning
confidence: 99%
“…[38] The Raman spectrum is formed mainly of a band at ~1040 cm -1 which is assigned to PO3 symmetric stretching modes of P2(O,F)7 dimers, in Q (1) units, and a band at 1110 cm -1 , assigned to PO2 stretching modes of metaphosphate groups. The band near 900 cm -1 suggest the existence of P-F bonding, [39,40] and the band observed near 740 cm -1 is assigned to the P-O-P symmetric stretching mode of bridging oxygen between two phosphate tetrahedral in short chains, such as Q (1) species. At lower frequency, the bands in the region 450-650 cm -1 are typically bands of alkaline-earth bonded to fluorine species observed in pure fluoride glasses.…”
Section: Structural Evolution Of the Glass After Polingmentioning
confidence: 98%
“…Upconversion-luminescent materials can achieve the conversion of infrared light into visible light. They exhibit promising applications in various fields such as solid-state lasers, information storage and processing, sensing and biological imaging, lighting sources, and three-dimensional (3D) displays. Transparent fluorophosphate glass-ceramics containing fluoride nanocrystals are excellent upconversion-luminescent materials that possess the advantages of good chemical stability and mechanical properties of oxide glass, low phonon energy of fluoride crystal, and high solubility of rare-earth ions of phosphate glass. , Glass-ceramics can be prepared by heating a precursor glass at the desired temperature; they can be easily processed into optical fibers, large blocks, and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Moncke and Eckert did a lot of work on the structural analysis of fluorophosphate glasses. 13 They applied a 31 P/ 23 Na and 31 P/ 19 F double-resonance nuclear magnetic resonance (NMR) strategy to glasses in the system (BiF 3 ) y (50NaPO 3 −20Ba(PO 3 ) 2 −20NaF−10BaF 2 ) 100−y 12 and found that the successive reduction of the dipolar second moment M 2 (Na−P) with increasing BiF 3 content reflected increasing competition of fluoride ions for ligation with Na + ions. They also applied 19 F/ 23 Na double-resonance NMR in Na 2 O−ZnO−Al 2 O 3 −SiO 2 −KBr glasses 14 and revealed that about 1/3 of the Na + ions have fluoride ions in their first coordination spheres.…”
Section: Introductionmentioning
confidence: 99%